In addition to full 3D views with perspective projections the program also has simpler 2D windows using Orthographic projection. This is to allow CAD type applications and applications where full 3D rendering is not required or is not supported.

To do this we need to represent 3D shapes, such as a cylinder, by using 2D shapes such as ellipse and lines.

We want to find the furthest and nearest points to the translation of the top to the 2D plane.

So we need to find the minima and maxima of:

f = (v - topv)+(u - topu)

subject to the constraint that:

g(u,v) = x+z- r= 0

we also know

u = m00 x + m01 y + m02 z + m03

v = m10 x + m11 y + m12 z + m13

g / u = ( g / x )( x / u ) + ( g / y )( y / u )

g / v = ( g / x )( x / v ) + ( g / y )( y / v )

sustitute following values in above

g / x = 2x

g / y = 2y

x / u = 1/m00

y / u = 1/m01

x / v = 1/m10

y / v = 1/m11

therefore:

g / u = 2x / m00 + 2y / m01

g / v = 2x / m10 + 2y / m11

expanding out f = (v - topv)+(u - topu) gives:

f = v - 2 v topv + topv) + u - 2 u topu + topu)

f / u = 2u - 2 topu

f / v = 2v - 2 topv

(2u - 2 topu) = (2x / m00 + 2y / m01)

(2v - 2 topv) = (2x / m10 + 2y / m11)

therefore

-= (u - topu) / (x/m00 + z/m02) = (v - topv) / (x/m10 + z/m12)

(m00 x + m01 y + m02 z + m03 - topu) * (x/m10 + z/m12) = (m10 x + m11 y + m12 z + m13 - topv) * (x/m00 + z/m02)

(m00/m10) x+ (m02/m10) x z + ( m01 y + m03 - topu)x/m10 + (m00/m12) x z + (m02/m12) z + ( m01 y + m03 - topu)z/m12 =

(m10/m00 x + m12/m00 x z + ( m11 y + m13 - topv) x/m00 + m10/m00 x z + m12/m00 z + ( m11 y + m13 - topv) z/m02

(m00/m10 - m10/m00) x+ (m02/m10 + m00/m12 - m12/m00 - m10/m00) x z + ( m01/m10 y + m03/m10 - topu/m10 - m11/m00 y - m13/m00 + topv/m00)x

+ (m02/m12 - m12/m00) z + ( m01/m12 y + m03/m12 - topu/m12 - m11/m02 y - m13/m02 + topv/m02)z =0

combine this with:

x+z= r

gives

(m00/m10 - m10/m00) x+ (m02/m10 + m00/m12 - m12/m00 - m10/m00) x sqrt(r- x) + ( m01/m10 y + m03/m10 - topu/m10 - m11/m00 y - m13/m00 + topv/m00)x

+ (m02/m12 - m12/m00) (r- x) + ( m01/m12 y + m03/m12 - topu/m12 - m11/m02 y - m13/m02 + topv/m02)sqrt(r- x) =0

This is an equation containing x and all the other variables are constants

so in theory its solvable, but I dont know how?

Attempt to solve this in terms of u and v, but I don't think this will work becase the 3d to 2d transform is not reversable. constraints: g(u,v) = x+z-r where: x = I00 u + I01 v + I02 y = I10 u + I11 v + I12 z = I20 u + I21 v + I22 not sure we can use this? can't derive x,y,z form screen coordinates! g(u,v) = (I00 u + I01 v + I02)+( I20 u + I21 v + I22)- r=0 expanding gives: g(u,v) = I00u + 2 I00 I01 v u + I01v + I02+ 2 I00 I02 u + 2 I01 I02 + I20u + 2 I20 I21 v u + I21v + I22+ 2 I20 I22 u + 2 I21 I22 - r=0 partial differentials are: g/u = 2 (I00 + I20)u + 2v (I00 I01 + I20 I21) + 2 (I00 I02 + I20 I22) g/v = 2 (I01 + I21)v + 2u (I00 I01 + I20 I21) + 2 (I01 I02 + I21 I22)
f/u = 2u - 2 topu f/v = 2 v - 2 topv using Lagrange 2u - 2 topu +( 2 (I00 + I20)u + 2v (I00 I01 + I20 I21) + 2 (I00 I02 + I20 I22)) = 0 2 v - 2 topv +( 2 (I01 + I21)v + 2u (I00 I01 + I20 I21) + 2 (I01 I02 + I21 I22)) = 0 divide both sides by 2: u - topu +( (I00 + I20)u + v (I00 I01 + I20 I21) + (I00 I02 + I20 I22)) =0 v - topv +( (I01 + I21)v + u (I00 I01 + I20 I21) + (I01 I02 + I21 I22)) =0 1/=( (I00 + I20)u + v (I00 I01 + I20 I21) + (I00 I02 + I20 I22)) / topu -u 1/=( (I01 + I21)v + u (I00 I01 + I20 I21) + (I01 I02 + I21 I22)) / topv -v
( (I00 + I20)u + v (I00 I01 + I20 I21) + (I00 I02 + I20 I22)) / topu -u = ( (I01 + I21)v + u (I00 I01 + I20 I21) + (I01 I02 + I21 I22)) / topv -v
( (I00 + I20)u + v (I00 I01 + I20 I21) + (I00 I02 + I20 I22)) * topv -v = ( (I01 + I21)v + u (I00 I01 + I20 I21) + (I01 I02 + I21 I22)) * topu -u
(I00 + I20)uv + v (I00 I01 + I20 I21) + (I00 I02 + I20 I22) v- (I00 + I20)u* topv - v (I00 I01 + I20 I21)* topv - (I00 I02 + I20 I22) * topv = (I01 + I21)vu + u (I00 I01 + I20 I21) + (I01 I02 + I21 I22)u - (I01 + I21)v* topu - u (I00 I01 + I20 I21)* topu - (I01 I02 + I21 I22)* topu
(I00 + I20-I01 - I21)uv + v (I00 I01 + I20 I21) + (I00 I02 + I20 I22) v- (I00 + I20)u* topv - v (I00 I01 + I20 I21)* topv - (I00 I02 + I20 I22) * topv = u (I00 I01 + I20 I21) + (I01 I02 + I21 I22)u - (I01 + I21)v* topu - u (I00 I01 + I20 I21)* topu - (I01 I02 + I21 I22)* topu combine with: g(u,v) = I00u + 2 I00 I01 v u + I01v + I02+ 2 I00 I02 u + 2 I01 I02 + I20u + 2 I20 I21 v u + I21v + I22+ 2 I20 I22 u + 2 I21 I22 - r=0 gives: I give up |